Phytochemical investigation on the fruits of Camptotheca acuminata and their chemotaxonomic significance. (December 2020) - Chang, Ye; Bai, Ming; He, Huan; Huang, Shun-Wang; Song, Shao-Jiang
Abstract: A phytochemical investigation on the fruits of Camptotheca acuminata led to the isolation of 13 compounds, including five coumarins (1 –5 ), two alkaloids (6 and 7 ), two triterpenoids (8 and 9 ), three lactones (10 –12 ) and a sesquiterpene (13 ). The structures of these compounds were elucidated by extensive spectroscopic methods and comparion with literature data. All compounds were isolated from the Nyssaceae family for the first time. Additionally, it should be noted that this is the first report of coumarins in the C. acuminata . The chemotaxonomic significance of the isolated compounds was summarised. Highlights: Coumarins (1 –5 ), alkaloids (6 and 7 ), triterpenoids (8 and 9 ), lactones (10 –12 ) and a sesquiterpene (13 ) were isolated from the fruits of Camptotheca acuminata. All compounds were obtained from the Nyssaceae family for the first time. Chemotaxonomic significance of these compounds was summarised.